Vistabeans coffee shop data analytics teaching case. (September 2016) - Igou, Amy; Coe, Martin
Highlights: The case uses data from a fictional nationwide coffee shop. Provides introduction to data analytics for use in an Accounting Information Systems course. Requires students to create data visualizations. Requires students to provide recommendations based on the data. Abstract: This case engages you in a data analytics learning activity. You will use data analytics software and a sample dataset to gain an understanding of data analytics and how data analytics can be used to answer important business questions from an accountant's perspective. The intended audience is accounting information systems course students.